Gender and popular culture - Milestone, Katie; Meyer, Anneke, 1976- (Cambridge : Polity Press, 2012)
A clear, comprehensive overview that examines how popular culture affects the construction of gendered identities. Up-to-date examples make key concepts and theories interesting and relevant for students. A mix of primary and secondary research creates a balanced yet original overview.
Includes bibliographical references (p. [215]-231) and index.
Keywords: Popular culture; Femininity in popular culture; Masculinity in popular culture; Sex role